The effect of using learning to learn the skill Olatghani correction of jumping forward handball - Ahmed , Russell (Journal of Physical Education, 2010)
1."The impact of the use of learning to learn skills Olitghani correction of jumping to the front wheel hand" Ensure that current research objectives are:2.Identify the impact of the use of learning style Olitghani to learn some skills of correction of jumping to the front handball.3. Identify the differences between the experimental and control groups in tests of learning a skill dimensional correction of jumping forward handball among members of the research sample.4.The researcher used the experimental approach to the relevance and nature of the research, the sample consists of students in Phase II / Faculty of Physical Education, Baghdad University department of teaching and of their number (60) student of the school season (2008 2009), was coherence between the sample and the researcher Experimental Design The two groups control and experimental one, was tested in the research sample in the tests under consideration, and set the curriculum, which consists of 15 educational unit rate of 2 units of tuition per week, and has been the implementation of the tests tribal, and after the implementation of the curriculum, and then testing a posteriori the same way as the performance Tribal tests.5. The researcher concluded the following:6. The use of learning Olitghani contributed to a high degree, learn a skill correction of jumping the fore in the experimental group and the creation of learning style Olitghani adaptations of physical skill which contributed to raising the level of mastery of skill correction and reflected on the results of the tests a posteriori values contributed to the existence of differences between the post and posterior tests in the experimental group. That the use of learning Olitghani ability to pay self-assessment has educated them by making them responsible for the evaluation and correction of vulnerable groups, which reflected the level of learning the skills of correction.7.The researcher recommended the following:8. Need to use the learning curriculum Olitghani in lectures to learn the skills in handball correction because of its positive impact on learning and retention of these skills. And the need to increase the number of educational lessons Handball achieved through encouragement and give degrees of performance skill and good conduct studies similar to the learning style Olitghani for the rest of basic skills in volleyball to students of the Faculty of Physical Education with a view to updating the skills of the game.